A Methodological and Reporting Quality Assessment of Systematic Reviews/Meta-Analyses about Chinese Medical Treatment for Gastroesophageal Reflux Disease. (24th September 2020) - Lyu, Zipan; Huang, Zhongyu; Liu, Fengbin; Hou, Zhengkun
Abstract : Objective . To access the methodological and reporting quality of systematic reviews (SRs)/meta-analyses (MAs) about Chinese medical treatment for gastroesophageal reflux disease (GERD). Methods . The PubMed, Wanfang Data, China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Periodical Database (VIP), Chinese Biomedical (CBM), Web of Science, and Cochrane Library databases were searched from inception to June 2020. Two researchers independently screened the literature considering the eligibility criteria. Overview Quality Assessment Questionnaire (OQAQ), Assessment of Multiple Systematic Reviews 2 (AMSTAR 2), and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used to assess the methodological and reporting quality of the included reports. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was used to evaluate the level of evidence in each report. Results . Thirty-three SRs/MAs met the inclusion criteria. The OQAQ results showed that defects in the methodological quality of 17/32 reports were major, with scores of 3 points. Analyzing a single item as the object, search strategies (item 2), and risk of bias in individual studies (item 4) was considered poor. The AMSTAR 2 results showed that 25.4% of the items were not reported, and 7.8% of the items were only partially reported. The overall assessment of AMSTAR 2 showed the majority of systematic reviews and meta-analyses were of low/very low (31/33, 93.9%) methodological quality, with a lack of protocol registration and excluded study list. The PRISMA results showed that 19.9% of items were not reported, and 15.2% of items were only partially reported, due to a lack of protocol registration and study selection methods. The methodological and reporting quality of the included studies was generally poor. Evidence evaluation with GRADE showed that most (31/33) of the included studies had low or very low levels of evidence. Conclusion. The methodological and reporting quality of SRs/MAs about Chinese medical treatment for GERD is generally poor. The main problems included incomplete search strategies, risk of bias in individual studies, the lack of protocol registration and excluded study list, and incorrect study selection methods.